MCQs for general duty medical officers (GDMO) with explanatory answer - Kumar, Rajeev (Jaypee Brtohers Medical Publishers / The Health Sciences Publisher, 2016)
This is probably the first book in the market of any exam conducted in 2015. It will help to prepare for the examinations because it consists of the latest questions. The motto of bringing this book is that it will provide the latest explanatory answers of any exam held in 2015. It will help in solving questions of upcoming examinations. This book offers authentic questions of GDMO 2015 entrance examination till date with correct answers and exhaustive explanations. This book is added with detailed explanations with references from standard textbooks of MBBS and PG. For questions with more than one correct answers, references have been provided from multiple sources with our personal opinion. This will help the readers to answer correctly in entrance examination with balanced judgment. Most importantly book has concise topic at one place and refer all the questions related to this topic, from which question has been asked or there is probability of asking question in future. More information is provided in less space. The explanations provided in this book have been formulated after exhaustive discussion and scrutiny by our faculty members, students, and aspirants of PGMEEs who have been preparing or have appeared for different entrance examinations and/or have already succeeded.